2021
DOI: 10.3390/su13126656
|View full text |Cite
|
Sign up to set email alerts
|

Design of Capacitive Bridge Fault Current Limiter for Low-Voltage Ride-Through Capacity Enrichment of Doubly Fed Induction Generator-Based Wind Farm

Abstract: The increase in penetration of wind farms operating with doubly fed induction generators (DFIG) results in stability issues such as voltage dips and high short circuit currents in the case of faults. To overcome these issues, and to achieve reliable and sustainable power from an uncertain wind source, fault current limiters (FCL) are incorporated. This work focuses on limiting the short circuit current level and fulfilling the reactive power compensation of a DFIG wind farm using a capacitive bridge fault curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The proposed controls efficiently reduce the oscillations of the generator torque, as demonstrated in Figure 6c. Moreover, as seen in Figure 6d, the DC-link voltage fluctuations do not exceed 15% of the rated value, indicating that it remains consistent within limits (25). Similarly, once the fault is cleared, the DC-link voltage drops by no more than 5% of its rated value for a few milliseconds before returning to its rated value.…”
Section: Performance Of the Proposed Control Scheme For Symmetrical G...mentioning
confidence: 69%
See 3 more Smart Citations
“…The proposed controls efficiently reduce the oscillations of the generator torque, as demonstrated in Figure 6c. Moreover, as seen in Figure 6d, the DC-link voltage fluctuations do not exceed 15% of the rated value, indicating that it remains consistent within limits (25). Similarly, once the fault is cleared, the DC-link voltage drops by no more than 5% of its rated value for a few milliseconds before returning to its rated value.…”
Section: Performance Of the Proposed Control Scheme For Symmetrical G...mentioning
confidence: 69%
“…A combination of active crowbars installed at the rotor side and DC-link was designed and implemented to mitigate the impacts of the grid faults that can destroy the DC-link capacitor and cause massive current stresses on wind-power converters. The results showed that this crowbar combination efficiently controlled the transient rotor and stator currents as well as DC-link voltage variations within permitted limits (25), which were considered the criteria for successful LVRT implementation. Moreover, the electromagnetic torque oscillations were effectively suppressed.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Therefore, series dynamic braking resistors (SDBRs) [23,29,35], bridge type fault current limiters (BFCLs) along with resistive, inductive, and capacitive components [36,37], series resonance type FCL [34], as well as parallel resonance type FCL (PRFCL) [38] show superior performance in smoothing the different output parameters of DFIG-based WFs. Among all the other types of BFCLs, capacitive bridge type fault current limiter (CBFCL) has been one of the newest and more improved BFCL to improve the FRT by a significant margin [39][40][41]. Moreover, it provides commensurate reactive power needed to recover PCC voltage after fault occurrence, which none of the other BFCLs provides.…”
Section: Introductionmentioning
confidence: 99%